Remaking The Making: E.P. Thompson's Reception in Argentina and the Shaping of Labor Historiography - Poy Piñeiro, Lucas Martín (2016)
This article traces the reception of E.P. Thompson's work in Argentina over the past three decades. It explores the context in which Thompson was read by labor historians as a means to analyse the way in which the country's labor historiography was shaped over this period. It argues that, in the 1980s and the 1990s, against a context characterized by a crisis of the political left and a downturn in the labor movement, Thompson's appropriation was focused on his critique of Marxist "determinism". While this corresponded to similar developments in other countries, Argentinian labor historiography started to show a different path in the early 2000s, when a tremendous social, political, and economic crisis shook the country. The article concludes that recent developments in labor historiography in Argentina show a different pattern to those seen in the "Global North".